The Chungopoint Method : making the most of the students' effort to speak the foreign language in the classroom = El Método Chungopoint : aprovechando al maximo el esfuerzo de los estudiantes para hablar el lenguaje extranjero en la clase - Rubio Alcalá, Fernando D. (2006)
Making students speak a foreign language (FL) in the classroom is considered to be a difficult task for teachers all around the world. In a typical classroom, students tend to avoid speaking a FL for several reasons. This prompts teachers to look for new ideas to motivate their students towards an oral practice. A wide range of activities which work just for a single situation are available, but few general methods for encouraging verbal production of FL can be found. This article proposes a possible alternative: the Chungopoint (Rubio y Petidier 2002), a method devised to use at anytime with oral activities no matter the structures or points involved. By using this method, students find themselves interacting in the FL in a playful way. When language students get used to it, oral activities become a natural, desired, and meaningful part of the class
En Revista Actualidades Investigativas en Educación, vol. 6, no. 2 (mayo - agosto 2006)
Descripción basada en el contenido visto el 30 de agosto, 2024